Price behaviour of black pepper in Indian and international markets: a comparative analysis - A Kuruvila, S S Sabu,; Manojkumar, K (Journal of Spices and Aromatic Crops, 2019)
Black pepper, being a trade dependent commodity, shows high degree of price fluctuations. The present study examined the price behavior of black pepper in the pre-liberalisation and postliberalisation periods. The study revealed that the variation in prices increased in the postliberalisation period. Seasonal nature was evident in prices and the harvesting period was found to be coinciding with the trough phase in the price cycle, while the off-season synchronized with the peak phase. The prices exhibited cyclical behavior and the periods of low prices endured longer than that of the price spikes. The occurrence and amplitude of random factors exhibited in the prices of black pepper were more in the pre-liberalisation period.